Hypoglycaemia is reduced with use of inhaled Technosphere(®) Insulin relative to insulin aspart in type 1 diabetes mellitus - Seaquist, E. R. (Diabet Med, 2019)
AIM: To evaluate the effect of final HbA(1c) levels on the incidences of hypoglycaemia in participants with type 1 diabetes treated with inhaled Technosphere(®) Insulin or subcutaneous insulin aspart, reported in alignment with the International Hypoglycaemia Study Group recommendations. METHODS: In the randomized, phase 3, multicentre AFFINITY‐1 study, adults (N = 375) who had type 1 diabetes for ≥ 12 months and an HbA(1c) level of 58–86 mmol/mol (7.5–10.0%) were randomized to receive basal insulin plus either inhaled Technosphere Insulin or subcutaneous insulin aspart. This was a post‐hoc regression analysis on a subset (N = 279) of the randomized AFFINITY‐1 cohort for whom baseline and end‐of‐treatment HbA(1c) values were reported. Primary outcome measures were incidence and event rates for levels 1, 2 and 3 hypoglycaemia, respectively defined as blood glucose levels of ≤ 3.9 mmol/l, < 3.0 mmol/l or requiring external assistance for recovery. RESULTS: Participants treated with Technosphere Insulin experienced statistically significantly fewer level 1 and 2 hypoglycaemic events and a lower incidence of level 3 hypoglycaemia than participants treated with insulin aspart. The lower rate of hypoglycaemia with Technosphere Insulin was observed across the range of end‐of‐treatment HbA(1c) levels. Technosphere Insulin was associated with higher rates of hypoglycaemia 30–60 min after meals, but significantly lower rates 2–6 h after meals. CONCLUSIONS: Participants using Technosphere Insulin experienced clinically non‐inferior glycaemic control and lower hypoglycaemia rates across a range of HbA(1c) levels compared with participants receiving insulin aspart. http://www.ClinicalTrials.gov: NCT01445951.